Universal Nature of Symbols as the Background of European Identity (on the Material of English and Ukrainian Phraseological Units): Array - Zhurkova, Olga (Journal of Danubian Studies and Research, 2020)
The problem of the symbol belongs simultaneously to the wide range of linguistic, philosophical, cultural and psychological issues. It is related to understanding the nature of language, more precisely to the problem of understanding as a process. Underlying motivation of phraseological units includes means indirectly related to the images of reinterpretation. One such means is symbolization. Universal standardization of images, including symbols or icons of worldview – is the result of the collective perception of the linguistic and cultural society of a particular experience.